Analysis of Micro And Small Business Marketing Strategy of Multi-functional Fertilizer Applicator (Malica) Using Swot Matrix - Khoirul Anam As Syukri; Moch Ezza; Muhammad Zamzami Al Mabruri; Sasongko Aji Wibowo (IQTISHADequity jurnal MANAJEMEN, 2022)
In general, one of the causes of fluctuations in agricultural productivity in Indonesia is still using conventional fertilization methods. This has an impact because of the risk of fatigue due to the conventional methods used. The Multifunctional Fertilizer Applicator (Malica) is a fertilization tool as well as sprinklers and pesticides that can be used as an applicator for liquid fertilizer and granular fertilizer using a spring valve mechanism as an output regulator. The research objective was to develop a marketing strategy for micro and small businesses using the Malika tool. To reach the predetermined target market and increase sales targets, an appropriate marketing strategy is needed. Marketing strategy analysis is carried out using the SWOT matrix based on internal and external business factors. Data collection was carried out through interviews, observation and literature study. The results of the IFAS and EFAS analysis have obtained an average IFE value of 2.79 and an average EFE value of 2.76. This value can indicate that this business is included in the cell V division which can use market penetration strategies and product development and the results of the SWOT analysis that has been carried out by linking internal factors and external factors obtained several competitive strategies including SO (Strengths-Opportunities) strategy, WO strategy (Weaknesses-Opportunities), ST strategy (Strengths-Threats), and WT strategy (Weaknesses-Threats). Of the 12 alternative strategies, there are 4 strategies chosen based on the highest weight, namely creating a business model that forms the foundation for developing the Malika product business, conducting business assessments from prospective customers and personal, conducting business branding by introducing products well to consumers and providing the best service to customers. consumer. So that this strategy can be used as a consideration in determining the marketing strategy of Malika's business.